EDITOR'S PREFACE - Achmad Zainal Arifin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Alhamdulillah, thank you be to Allah for the publication of Jurnal Sosiologi Reflektif (JSR) Vol.16 No.2 in 2022. After a little delay due to the moment of Ramadan and Eid Al-Fitr, JSR is able to greet all readers again. The outline of the article from this edition is the result of the 6th JSR Panel Conference held on November 24-25, 2021. The theme of the 6th panel conference is: